Right of Minors to Education and its Implementation in the National Legislation of the Russian Federation - BOLSHAKOVA, Oksana Gennadievna; KVITKOVSKAYA, Angelina Anatolievna; PROKHOROVA, Larisa Viktorovna; RABETS, Anna Maximovna; TCHINARYAN, Elena Olegovna (Journal of Advanced Research in Law and Economics; Vol 8 No 5 (2017): JARLE Volume VIII Issue 5(27) Fall 2017, 2018)
This work is devoted to problems of the legal status of children in establishment, preservation, realization and protection of the right for education at the international legal and national levels. Based on comparison of the international legal regulation of minors’ right to education and the existing federal legislation on education, the authors come to a conclusion about high degree of conformity of the national legislation of the Russian Federation to the generally accepted principles and rules of international law. Special attention is paid to the characteristics of the constitutional prerequisites of regulation and realization of minors’ right to education in the Russian Federation, and such political and legal program documents as Concept of long-term socio-economic development of the Russian Federation for the period until 2020, approved by the Order of the Government of the Russian Federation of November 17, 2008 No. 1662 (Order of the Government of the Russian Federation, 2008); National strategy of actions for the benefit of children for 2012-2017, approved by the Decree of the Russian President of June 1, 2012 No. 761 (Decree of the Russian President, 2012); Concept of the state family policy in the Russian Federation for the period until 2025, approved by the Order of the Government of the Russian Federation of August 25, 2014 No. 1618 (Order of the Government of the Russian Federation, 2014) and others. The attention is also paid to the specifics of realization of the right to education of various categories of minors, in particular, orphaned children, children deprived of parental care, children with limited health opportunities and convicted minors.